Pelanggaran dan Penyebab Permasalahan Hak Cipta Serta Pembayaran Royalti Lagu di Indonesia - Christopher Nahum Prama Muda; Albertus Sentot Sudarwanto (Referendum : Jurnal Hukum Perdata dan Pidana, 2025)
Copyright of songs or music has proven to be able to open up almost limitless financial opportunities. It is difficult to determine how much a song is used for commercial purposes by parties other than the original creator. A major challenge in the music industry is the fair and transparent distribution of copyright royalties for songs. To address this issue, it is important to explore international best practices and case studies that reveal successful royalty distribution models and technology-based solutions for accurate tracking and payment. Important aspects of a fair and transparent royalty distribution model include transparency in revenue sharing, fair allocation based on popularity and usage of songs, and simplification of the royalty collection process through technology. The research method used is normative legal research. This research is prescriptive and applied. The method of collecting legal materials is by means of literature study and the legal materials used are primary legal materials and secondary legal materials. This study evaluates the effectiveness of the implementation of Law Number 28 of 2014 concerning Copyright and Government Regulation Number 56 of 2021. This study also identifies the legal, technical, and social challenges faced in protecting the rights of songwriters and ensuring fair royalty payments.